Multiphysical contact of functionally graded magneto-electro-elastic material with imperfect bonding interface - Yijin Sui; Haibo Zhang; Jieliang Zhao; Wenzhong Wang (Friction, 2023)
Abstract Three-dimensional (3D) frictional contact model of functionally graded magneto-electro-elastic (FGMEE) material with a conducting spherical punch under electromagnetic fields is presented. Two types of imperfect bonding interface of layers, dislocation-like interface and force-like interface, are considered. Frequency response functions (FRFs) for multilayered MEE material with imperfect interface subjected to unit mechanical, electric, and magnetic loads are derived. The FRFs are used with the semi-analytical method (SAM) to solve present multiphysical contact problem. The present model is verified by comparing with literatures and the finite element method (FEM) and used to study the contact problem of FGMEE film imperfectly bonded on homogenous MEE half-space under electromagnetic fields. Parametric studies are conducted to reveal the effects of imperfect interfaces and also film properties including gradient index and thickness.